DNA barcoding of the genus Alburnoides Jeitteles, 1861 (Actinopterygii, Cyprinidae) from Anatolia, Turkey - Halim Canoglu; Ismail Aksu; Davut Turan; Yusuf Bektas (Zoosystematics and Evolution, 2023)
The present study investigated the ability of DNA barcoding to reliably identify the endemic freshwater species in Turkey, known as biodiversity hotspots. The barcode region (652 bp) of the mitochondrial cytochrome c oxidase subunit I (COI) was used to barcode 153 individuals from 13 morphologically identified species of the genus Alburnoides. Based on the Kimura two-parameter (K2P) evolution model, the average interspecific distance (0.0595) was 31-fold higher than the average intraspecific distance (0.0019). There was a clear-cut barcode gap (0.0158–0.0187) between maximum intraspecific distance (A. tzanevi and A. velioglui) and minimum nearest-neighbour distance (A. freyhofi and A. kurui) for Anatolian Alburnoides species and a common genetic threshold of 0.0158 sequence divergence was defined for species delimitation. The multiple species delimitation methods (ABGD, ASAP, GMYC and bPTP) revealed a total of 11 molecular operational taxonomic units (MOTUs) for 13 morphospecies. Neighbour-joining (NJ), Maximum Likelihood (ML) and Bayesian Inference (BI) tree analysis indicated that all haplotypes were clustered into two major clades, which corresponded to eleven Alburnoides species clusters, with strong bootstrap support. Furthermore, all the specimens clustered in concurrence with the morpho-taxonomic status of the species, except for two species (A. coskuncelebii and A. emineae) that were morphologically differentiated, but showed overlap in variation for COI-based DNA barcode data with other species. Overall, present results identified that COI-based DNA barcoding is effective for species identification and cataloguing of genus Alburnoides in Turkey.